Carfilzomib, lenalidomide and dexamethasone in patients with heavily pretreated multiple myeloma: A phase 1 study in Japan. Issue 3 (March 2017) - Suzuki, Kenshi; Ri, Masaki; Chou, Takaaki; Sugiura, Isamu; Takezako, Naoki; Sunami, Kazutaka; Ishida, Tadao; Izumi, Tohru; Ozaki, Shuji; Shumiya, Yoshihisa; Ota, Kenji; Iida, Shinsuke
Abstract : This is the first study in which the carfilzomib, lenalidomide and dexamethasone (KRd) regimen was evaluated in heavily pretreated multiple myeloma. This study is a multicenter, open‐label phase 1 study of KRd in Japanese patients with relapsed or refractory multiple myeloma (RRMM) patients. The objectives were to evaluate the safety, tolerability, efficacy and pharmacokinetics of the regimen. Carfilzomib was administrated intravenously over 10 min on days 1, 2, 8, 9, 15 and 16 of a 28‐day cycle. In cycle 1, the dosage for days 1 and 2 was 20 mg/m 2, followed by 27 mg/m 2 . Lenalidomide and dexamethasone were administered at 25 mg (days 1–21) and 40 mg (days 1, 8, 15 and 22), respectively. Twenty‐six patients were enrolled. Patients had received a median of four prior regimens and 88.5% and 61.5% received previous bortezomib and lenalidomide, respectively. High‐risk cytogenetics were seen in 53.8% of patients. The overall response rate was 88.5%. A higher rate of hyperglycemia was observed than in a previous carfilzomib monotherapy study, but this was attributed to dexamethasone. Carfilzomib pharmacokinetics were not affected by lenalidomide and dexamethasone. The KRd regimen was well tolerated and showed efficacy in Japanese RRMM patients. Abstract : We performed a multicenter, open‐label phase 1 study of the carfilzomib, lenalidomide, and dexamethasone (KRd) regimen in Japanese patients with heavily pretreated relapsed or refractory multiple myeloma (RRMM) to evaluate safety, tolerability, efficacy and pharmacokinetics. The overall response rate was 88.5%, and the regimen was well tolerated, showing efficacy in Japanese RRMM patients.